Dampak Penggunaan Gadget terhadap Kemampuan Interaksi Sosial Siswa pada Pembelajaran IPS Kelas IV SD Negeri 1 Jatigunung - Kusuma, Rizal Wijaya; Al Fath, Ayatullah Muhammadin; Burhanuddin, Afid (PGSD STKIP PGRI Pacitan, 2022)
The number of gadget users in elementary school students has recently increased. If this habit is sustainable, it can make students social interaction skills decrease. This study aims (1) to determine the gadget users for fourth-grade students at SD Negeri 1 Jatigunung, (2) students’ social interaction skills in social studies subjects for class IV SD Negeri 1 Jatigunung, and (3) the impact of using gadgets on students social interaction skills in social studies learning for fourth-grade students at SD Negeri 1 Jatigunung. The type of research was descriptive qualitative. Data collection techniques were observation, interviews, and documentation. The results of the study on fourth grade students of SD Negeri 1 Jatigunung, are as follows: (1) Grade IV students with a total of 26 students, including smartphone users; (2) the social interaction ability of fourth grade students during social studies learning in class is low; (3) The gadget users on students has a negative impact on students social interaction skills in social studies learning. The negative impacts were the unpolite students speaking to their teachers in less refined language (Javanese ngoko), students less confidence, students do not interact with friends, and students less focus when given the theory.